Shame as a Mediator Between Gender Norm Conflict and Emotional Distress in Muslim Women - Adeyemi, Ibrahim; Viteri, Camila (Psychology of Woman Journal, 2024)
Objective: This study aimed to investigate the mediating role of shame in the relationship between gender norm conflict and emotional distress among Muslim women. Methods and Materials: A descriptive correlational research design was used to examine the proposed relationships. The sample consisted of 502 Muslim women residing in Ecuador, selected based on the Krejcie and Morgan sample size table. Participants completed three standardized instruments: the Gender Role Conflict Scale (GRCS) to measure gender norm conflict, the Experience of Shame Scale (ESS) to assess shame, and the Depression Anxiety Stress Scales–21 (DASS-21) to measure emotional distress. Data were analyzed using SPSS-27 for descriptive and Pearson correlation statistics and AMOS-21 for structural equation modeling (SEM) to evaluate direct, indirect, and total effects among variables and assess model fit. Findings: Pearson correlation results indicated significant positive relationships between gender norm conflict and shame (r = .48, p < .001), shame and emotional distress (r = .55, p < .001), and gender norm conflict and emotional distress (r = .41, p < .001). The SEM analysis confirmed a good model fit (χ²/df = 2.53, CFI = .96, RMSEA = .054, TLI = .95). Gender norm conflict significantly predicted shame (β = .48, p < .001), and shame significantly predicted emotional distress (β = .51, p < .001). The direct effect of gender norm conflict on emotional distress was significant (β = .22, p = .004), and the indirect effect through shame was also significant (β = .24, p < .001), indicating partial mediation. Conclusion: The findings highlight shame as a significant emotional mechanism that partially mediates the effect of gender norm conflict on emotional distress in Muslim women. Addressing internalized shame may be critical for improving psychological well-being in populations experiencing tension with traditional gender roles.